Openness and Growth: The Long Shadow of the Berlin Wall - Claudia M. Buch; Farid Toubal (Institut für Angewandte Wirtschaftsforschung (IAW), 2007)
The question whether international openness causes higher domestic growth has been subject to intense discussions in the empirical growth literature. This paper addresses this issue using the fall of the Berlin wall in 1990 as a natural experiment. We analyze whether the slow-down in convergence in per capita income between East and West Germany since the mid-1990s and the lower international openness of East Germany are linked. We address the endogeneity of openness by adapting the methodology proposed by Frankel and Romer (1999) in a panel framework. We instrument openness with time-invariant exogenous geographic variables and time-varying exogenous policy variables. We also distinguish different channels of integration. Our paper has three main findings. First, geographic variables have a significant impact on regional openness. Second, controlling for geography, East German states are less integrated into international markets along all dimensions of integration considered. Third, the degree of openness for trade has a positive impact on regional income per capita.
Keywords: F43; F2; 330; openness; growth; German re-unification; Politik der offenen Tür; Außenhandelsliberalisierung; Wirtschaftswachstum; Nationale Einheit; Regionales Wachstum; Entwicklungskonvergenz; Alte Bundesländer; Neue Bundesländer; Deutschland